Using Interdisciplinary Dress Rehearsal Events to Ensure Staff Readiness When Opening a New Healthcare Facility. (January 2020) - Aguilera, Lynn S.; Dickey, Erica K.; Guzman, Kelly
Objective: This nonresearch article describes best practices of using the simulation-based Dress Rehearsal method to prepare staff to move into a new hospital or a new space in an existing facility and to ensure the new facility is ready for use. The authors introduce a modified version of the interactive sociotechnical analysis (ISTA) model to serve as the academic foundation for the Dress Rehearsal concept. Background: Healthcare organizations that build new medical facilities must ensure the space is ready to use and that all staff, who will deliver and support patient care, are sufficiently trained. Currently, no standardized approach exists to prepare staff on an interdisciplinary level, to work in their new environment. There are multiple articles highlighting a single hospital or department using simulations before opening, but there is a lack of literature from an aggregate perspective. Method: The Dress Rehearsal method is examined by drawing from the author's combined experience of conducting and evaluating hundreds of Dress Rehearsals across North America. Best practices to plan, prepare, and execute events will be reviewed. Results: Evaluations collected after each event present a positive impact related to staff feeling prepared to provide safe care in the new environment, with increased satisfaction after subsequent Dress Rehearsals. Conclusions: A standardized approach to ensure staff feel confident and safe to move into their new healthcare environment should be a top priority for healthcare leadership. The Dress Rehearsal method is a substantive strategy that supports building and staff readiness for opening day and beyond.